Development of the pyruvate kinase deficiency diary and pyruvate kinase deficiency impact assessment: Disease‐specific assessments. (24th February 2020) - Salek, Sam; Boscoe, Audra N.; Piantedosi, Sarah; Egan, Shayna; Evans, Christopher J; Wells, Ted; Cohen, Jennifer; Klaassen, Robert J.; Grace, Rachael; Storm, Michael
Abstract: Introduction: Currently recommended patient‐reported outcome (PRO) measures for patients with pyruvate kinase (PK) deficiency are non‐disease‐specific. The PK Deficiency Diary (PKDD) and PK Deficiency Impact Assessment (PKDIA) were developed to be more targeted measures for capturing the symptoms and impacts of interest to this patient population. Methods: The instruments were developed based on concept elicitation interviews with 21 adults and modified based on 20 cognitive interviews. The domain structure and item concepts of the PKDD and PKDIA were compared with currently recommended measures, the EORTC QLQ‐C30 and the SF‐36v2®. Results: The PKDD is a seven‐item measure of the core signs and symptoms of PK deficiency. The PKDIA is a 14‐item measure of the impacts of PK deficiency on patients' health‐related quality of life (HRQoL). Minimal similarities were found between the new measures and the EORTC QLQ‐C30 (eg, 43% of concepts were similar to the PKDD; 42% were similar to the PKDIA) and SF‐36v2® (57% of concepts were similar to the PKDD; 17% were similar to the PKDIA). Conclusions: The PKDD and PKDIA fill a gap in the existing outcomes measurement strategy for PK deficiency. Future work includes psychometric evaluation of these newly developed measures.